2020
DOI: 10.3389/fpls.2020.586470
|View full text |Cite
|
Sign up to set email alerts
|

FePO4 NPs Are an Efficient Nutritional Source for Plants: Combination of Nano-Material Properties and Metabolic Responses to Nutritional Deficiencies

Abstract: Phosphorous and iron are a macro- and micronutrient, respectively, whose low bioavailability can negatively affect crop productivity. There is ample evidence that the use of conventional P and Fe fertilizers has several environmental and economical disadvantages, but even though great expectations surround nanotechnology and its applications in the field of plant nutrition, little is known about the mechanisms underlying the uptake and use of these sub-micron particles (nanoparticles, NPs) by crop species. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…However, there is a need more investigation for P. vittata and phyto siderophores role in FePO 4coll dissolution. Our results agreed with Sega et al (2020) who claimed that root exudation may dissolute the FePO 4 nano particles which release P and Fe. However, they did not mention which organic acid can dissolute the FePO 4 .…”
Section: Role Of Phytate In Fepo 4coll Dissolutionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, there is a need more investigation for P. vittata and phyto siderophores role in FePO 4coll dissolution. Our results agreed with Sega et al (2020) who claimed that root exudation may dissolute the FePO 4 nano particles which release P and Fe. However, they did not mention which organic acid can dissolute the FePO 4 .…”
Section: Role Of Phytate In Fepo 4coll Dissolutionsupporting
confidence: 93%
“…Colloidal P and Fe are frequently associated (Niyungeko et al, 2018;Fresne et al, 2021b, Jiang et al, 2015, and affect the uptake of P from colloids (Montalvo et al 2015); Zhang et al, 2021). In addition, Sega et al (2020) claimed that organic acid exudation may dissolve nano FePO 4 and release P for plant uptake; however, they did not identify which organic acids may be involved. However, the above mentioned studies did not mention the potential role of phytate exudation in dissolution of FePO 4coll .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, cucumber roots were not able to take up the nFe, possibly due to agglomeration. These comparative results clearly indicate that the nutrient utilization of roots exposed to FeSO 4 NPs is affected by species-specific metabolic responses ( Sega et al , 2020 ).…”
Section: Promoting Effects Of Essential Nanometals On Non-metal-accum...mentioning
confidence: 83%
“…Differently, the higher initial P availability caused by TSP mainly depends on the soil P buffer capacity: the release of P in the soil solution triggered by the plant root induced modi cation of the chemical equilibrium between phosphates and the soil solid phases (Ehlert et al 2003). Globally, in terms of P fractionation in soil the main difference between TSP and NF is: for TSP it is in uenced by its dissolution rate and eventual salt precipitation due to the soil properties whereas for NF the P fractions depend more on the physico-chemical properties of the nanoparticles which could be solubilized by the root activity depending on the plant nutritional demand (Sega et al 2020;Khan et al 2022). This hypothesis could be supported by the results reported by Montalvo et al (2015) who showed in two strongly P sorbing soils a higher P uptake in roots of wheat plants fertilized with TSP as compared to plants fertilized with hydroxyapatite nanoparticles, a less soluble P form.…”
Section: Discussionmentioning
confidence: 99%